In silico study of dimethyltryptamine analogues against 5-HT1B receptor: Molecular docking, dynamic simulations and ADMET prediction - Neyder Contreras; Antistio Alvíz-Amador; Isabella Manzur-Villalobos (Shahrekord University of Medical Sciences, 2022)
Introduction: The 5-HT1B receptor has a potential role in various psychiatric disorders such as depression, anxiety, and post-traumatic stress disorder. The objective of this study was to perform docking and molecular dynamics simulation to evaluate at atomic level the behavior of N,N-dimethyltryptamine (DMT) on 5-HT1B receptor.Methods: In this study, initially, a search for DMT was performed using the PubChem database. Subsequently, molecular docking was executed using AutoDock Vina based in PyRx 0.8 with a 95% analogy. Additionally, ergotamine (ERG) and serotonin were used as control. Then, it ran a total of 100 ns molecular dynamics simulations on 5-HT1B bound with DMT, serotonin, 112814775, and ERG. Finally, pharmacokinetic prediction and IV acute toxicity for analogues and DMT were performed.Results: It was possible to show that 112814775 had the lowest binding energy with the receptor. In addition, 112814775 presented great conformational stability, low mobility, and stiffness compared to the control ligands: ERG, serotonin, and DMT subsequent dynamic analysis. With respect to the free energy calculation, contributions such as Van der Waals, electrostatics, and nonpolar interactions for all systems, were highlighted.Conclusion: 112814775 showed affinities with 5-HT1B receptor and evidenced notable behavior by molecular dynamic simulation according to root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), solvent-accessible surface area (SASA), the radius of gyration, number of hydrogen bond, and free energy calculated. These results established the possible relevance of in-silico studies in search of DMT analogues against the 5-HT1B receptor, which may be associated with alterations such as depression and anxiety, and may become future study molecules for the treatment of this type of disorder.